Meningkatkan Kompetensi Pengetahuan IPA Melalui Model Pembelajaran Kooperatif Tipe Scramble Terhadap Siswa Kelas VI Sekolah Dasar - Riska Kurniawati, Ni Putu (Journal for Lesson and Learning Studies, 2022)
At this time, many students still feel bored and need help understanding the learning material carried out in class, especially in learning science. It is because the learning activities carried out in the classroom are still centered on the teacher, so students feel bored quickly and are less enthusiastic when participating in activities. This study aimed to determine the effect of the Scramble Type Cooperative Learning Model on the Science Knowledge Competence of Sixth Grade Elementary School Students. This type of research is quantitative with a quasi-experimental design. The population in this study was 448 students of sixth-grade elementary school. Sampling was done using the cluster random sampling technique, with the final sample being 28 students as the control group and 28 as the experimental group. Data collection in the study was carried out using the test method, with an objective test research instrument in the form of multiple choices. The techniques used to analyze the data were descriptive statistical and inferential statistics. The results showed significant differences in the competence of science knowledge between students who were treated using the Scramble Type Cooperative learning model and students who were not given the treatment in the form of the Scramble Type Cooperative learning model. Based on these results, the Scramble Type Cooperative learning model has a significant positive impact on increasing the competence of science knowledge in elementary school students.